Tabung masjid - Wan Fadhli, Wan Ismail (2009)
Mosque fund use wheel seldom seen in several mosque to collect fund raising. With are wheel placed beneath this mosque fund, it would facilitate this mosque fund can be moved by shelf Islamic from one place to one another place. Hereby also, shelf Islamic no need move and find mosque fund because shelf Islamic can move mosque fund to raise fund. This is because seem shelf Islamic continuous going in a crowd to mosque fund previously difficult to be moved especially when prayer time Friday. To ease shelf Islamic which wanted donate some alms, put wheel in mosque fund is one creativity